PHYLOGENETIC ANALYSIS AND VIRULENCE-CODING GENES CHARACTERIZATION OF NEWCASTLE DISEASE VIRUS ISOLATED FROM LAYING HEN BRAIN WITH TETELO SYMPTOM - Safira Iqlima Sarah; Christian Marco Hadi Nugroho; Ryan Septa Kurnia; Dhandy Koesoemo Wardhana; Heni Puspitasari (Universitas Syiah Kuala, 2019)
Newcastle disease (ND) is an acute poultry disease caused by Paramyxovirus group. It has characteristic neurological symptoms, called torticollis. The molecular assay to find out the presence of viral genes in the brain can be an option in detecting ND virus infections since it penetrates brain barrier system. The purpose of this study was to identify ND viruses in the brain of chickens with torticollis symptoms, to analyze its phylogenetic and to characterize its virulence genetic code. Samples used were 12 dead chickens with historically had torticollis symptoms, obtained from poultry farms at several areas in West Java and Banten. Chicken brains were prepared for reverse transcriptasepolymerase chain reaction (RT-PCR) test. All positive samples then sequenced to obtain its nucleotide sequences from some of Fusion (F) genes analyzed its phylogenetic by comparing with Indonesian ND isolate virus from GenBank using Mega X software. The results of RT-PCR test showed that only one sample (Virus MSL.03) contained genes of ND virus. Based on homology tests and phylogenetic analysis, the virus belonged to subgenotype VIIh with an identical level of 95.34-95.86% when compared to several isolates from Indonesia. The MSL.03 ND virus has 112RRRKRF117 pattern in F0 indicatest its virulent category.